2017
DOI: 10.1038/s41598-017-03963-8
|View full text |Cite|
|
Sign up to set email alerts
|

The efficacy and toxicities of intensive induction chemotherapy followed by concurrent chemoradiotherapy in nasopharyngeal carcinoma patients with N3 disease

Abstract: To assess the feasibility, efficacy and safety of 4 cycles of induction chemotherapy (ICT) followed by concurrent chemoradiotherapy (CRT) in nasopharyngeal carcinoma (NPC) patients with N3 disease. ICT consisting of paclitaxel (135 mg/m2) and nedaplatin (80 mg/m2) given every 3 weeks for 4 cycles followed by cisplatin-based CRT was planned. 22 patients completed 4 cycles of TP regimen ICT and the CRT according to the protocol. After 4 cycles of ICT, the ORR of the primary site was 100% (CR 22.7%, PR 77.3%), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Interestingly, the same results were found in stage IVA patients. In previous studies, patients with advanced N category (N2-3) were more prone to distant metastasis (21); in our N category subgroups, fortunately, we observed that the TPF group had a trend in higher 5-year DMFS (P = 0.057), which was not applicable in N0-1. One possible statement is that TPF can reduce distant metastases from patients with high metastatic burdens (N2-3).…”
Section: Discussioncontrasting
confidence: 66%
“…Interestingly, the same results were found in stage IVA patients. In previous studies, patients with advanced N category (N2-3) were more prone to distant metastasis (21); in our N category subgroups, fortunately, we observed that the TPF group had a trend in higher 5-year DMFS (P = 0.057), which was not applicable in N0-1. One possible statement is that TPF can reduce distant metastases from patients with high metastatic burdens (N2-3).…”
Section: Discussioncontrasting
confidence: 66%
“…However, the number of cycles of NAC that should be recommended for these patients is unclear. In previous studies [ 12 17 ], NPC patients received 2, 3, and even 4 cycles of NAC. More cycles of NAC delay IMRT delivery and prolong the wait time of IMRT.…”
Section: Introductionmentioning
confidence: 99%
“…Four cycles of IC were effective and well tolerated. 29 A trial on 4 cycles of neoadjuvant chemotherapy plus concurrent chemoradiation in N2-3 nasopharyngeal carcinoma is ongoing (NCT02512315). EBV DNA is the most effective prognostic biomarker for guiding the treatment of NPC.…”
Section: Discussionmentioning
confidence: 99%